Qi-fu-yin attenuated cognitive disorders in 5xFAD mice of Alzheimer's disease animal model by regulating immunity - Yang, Xiuzhao; Ye, Tianyuan; He, Yun; Wen, Lei; Cheng, Xiaorui (Frontiers in Neurology, 2023)
Introduction Cognitive impairment is the main symptom of Alzheimer's disease (AD). Accumulating evidence implicate that immunity plays an important role in AD. Here, we investigated the effect of Qi-fu-yin (QFY) on cognitive impairment and cytokine secretion of 5xFAD mice. Methods We used 2.5-month-old 5xFAD transgenic mice for behavioral tests to observe the changes in cognitive function after QFY treatment. After the behavioral experiment, the whole brain, cortex and plasma of each mouse were collected for soluble Aβ analysis, immunohistochemical experiment and cytokine analysis. Results Here we found that the treatment of QFY ameliorated the ability of object recognition, passive avoidance responses and the ability of spatial learning and memory in 5xFAD mice. The deposits of β1 − 42 and Aβ1 − 40 were alleviated and the ration of Aβ1 − 42/Aβ1 − 40 was decrease in the plasma and brain of 5xFAD mice administrated with QFY. The administration of QFY promoted the secretion of anti-inflammatory cytokines, IL-5, IL-10 and G-CSF, and reduced the content of proinflammatory cytokines IFN-γ in plasma of 5xFAD mice. Notably, we found that the treatment of QFY decreased the concentration of CCL11 in the brain and plasma of 5xFAD mice. Conclusion This suggested that QFY improved cognition and reduced Aβ deposits in 5xFAD mice by regulating abnormal immunity in 5xFAD mice. QFY may be as a potential therapeutic agent for AD.